2018
DOI: 10.1111/cxo.12667
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of early retinal changes in children with type 1 diabetes mellitus without retinopathy

Abstract: Retinal neural changes, which can be shown by SD-OCT, may be present in diabetic eyes even before clinically detectable retinal vasculopathy. Macular and RNFL thickness measurements might be useful indicators for early detection of diabetic retinopathy in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
5
21
0
Order By: Relevance
“…The least amount of significant cells was detected for INL in both studies. These results are in accordance with results of other studies that reported thickness reduction of inner retinal layers in patients with T1DM (e.g., works by the authors of [29,36,37]) or T2DM (e.g., works by the authors of [35,38]) as an early event of neurodegenerative change.…”
Section: Grid-based Analysis Of Retinal Layer Thickness In Patients Wsupporting
confidence: 93%
“…The least amount of significant cells was detected for INL in both studies. These results are in accordance with results of other studies that reported thickness reduction of inner retinal layers in patients with T1DM (e.g., works by the authors of [29,36,37]) or T2DM (e.g., works by the authors of [35,38]) as an early event of neurodegenerative change.…”
Section: Grid-based Analysis Of Retinal Layer Thickness In Patients Wsupporting
confidence: 93%
“…Quantification of perfused retinal capillaries may prove valuable for developing sensitive biomarkers to earlier diagnose and monitor the progression of ocular and systemic diseases. 4,5,[12][13][14] The quantification of capillary parameters typically requires a segmented, binary image. Although manual segmentation of the capillaries in grayscale AOSLO or OCTA images can be performed, such a procedure is largely subjective and requires many hours for completion by a skilled observer.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Optical coherence tomography (OCT) has shown reduced thickness of the retinal nerve fiber and ganglion cell layers in children with T1DM without retinopathy, which is suggestive of early neuronal damage. [6][7][8] Furthermore, in vivo corneal confocal microscopy (IVCCM), a rapid noninvasive ophthalmic imaging technique has also been shown to identify early corneal cellular and nerve fiber pathology in children and adolescents with T1DM, 9 adults with T1DM without neuropathy, 10 or retinopathy or microalbuminuria. 11 Furthermore, reduced corneal nerve fiber length predicts the development of clinical diabetic neuropathy 12 and the development or worsening of retinopathy.…”
mentioning
confidence: 99%